Sinergi Pemerintah dan Perguruan Tinggi: Strategi Relevan untuk Peningkatan Kualitas SDM Berkelanjutan - Elfisa, Yesi; Akbar, Muhammad Tulus (PT. Meja Ilmiah Publikasi, 2025)
Access to quality education is a fundamental right of every citizen and is guaranteed by the 1945 Constitution of Indonesia. To realize education that is both character-driven and aligned with local cultural values, structured regulations and appropriate policies are required to ensure alignment with established educational frameworks. This community service activity aims to explore and strengthen the collaboration between local government and higher education institutions in formulating strategies to sustainably improve the quality of human resources (HR). A descriptive qualitative approach was employed, gathering insights and perspectives from key stakeholders directly involved in the education sector. Data were collected through observation, interviews, and documentation, involving representatives from local government, education practitioners, academics, members of the Islamic Students Association (HMI) Bangko Branch, students from Universitas Merangin and IAI Syeh Maulana Qory, as well as independent local journalists. The involvement of various sectors was intended to enrich the discourse and produce applicable solutions to existing educational challenges. The findings highlight the need for synergy among all stakeholders to establish an inclusive, adaptive, and competitive education system. Through this collaborative approach, it is expected that the development of superior, creative, and globally competitive human resources can be achieved. This activity emphasizes the importance of transforming the education system by strengthening the collective role of all parties involved in order to respond effectively to the demands of globalization and societal change.